Pengaruh Penerapan Konsep Basis Akuntansi Sektor Publik Dalam Rencana Anggaran Keuangan Daerah Pada Pemerintah Kota Malang - Nurul Baity; Syamsul Bahri; Endah Puspitosarie (CV. ITTC INDONESIA, 2025)
This study aims to analyze the influence of the implementation of public sector accounting basis concepts, particularly cash basis and accrual basis, on the quality of regional financial budget planning in the Malang City Government. The background of this research is driven by the demand for regional financial reform through the application of accrual-based Government Accounting Standards (SAP) as mandated by Government Regulation No. 71 of 2010, which emphasizes the importance of transparency, accountability, and effectiveness in managing regional budgets (APBD). This research employs a quantitative approach using a survey method through questionnaires distributed to government officials directly involved in budget preparation. The data were analyzed using multiple linear regression to test the effect of independent variables on the dependent variable. The results show that the implementation of both cash basis and accrual basis has a significant influence, both partially and simultaneously, on the quality of regional budget planning. These findings affirm that consistent implementation of accounting bases in accordance with standards not only improves fiscal data accuracy but also strengthens transparent and accountable financial governance while supporting the effectiveness of regional development.